2020
DOI: 10.1002/anie.202009797
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbituril‐Based Biomacromolecular Assemblies

Yao‐Hua Liu,
Ying‐Ming Zhang,
Hua‐Jiang Yu
et al.

Abstract: The construction of controlled biomacromolecular assemblies has become a thriving area of supramolecular chemistry. In this context, cucurbiturils (CBs), a class of macrocyclic receptors having robust skeletons, hydrophobic cavities, and carbonyl‐laced portals, have been drawn into the limelight because of their advantageous molecular recognition characteristics with a variety of biomacromolecules, including peptides, nucleic acids, and proteins. In this minireview, we focus on the impressive advances in CB‐ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(158 citation statements)
references
References 111 publications
(71 reference statements)
1
154
0
1
Order By: Relevance
“…[4,6] On account of high binding affinity and the wide scope of guests, cucurbit[n]uril (CB[n])-mediated host-guest complexes are ideal systems to bind peptides. [15][16][17][18][19][20] Urbach et al found that two FGG tripeptides can be complexed with CB [8] to form a peptide homodimer, exhibiting high binding strength (K ≈ 10 11 M -2 ). [15] This type of homodimer has been adopted as a versatile building block in the design and fabrication of supramolecular oligomers [21] and † These authors contributed equally to this work.…”
Section: Dimerization Of Peptides Through Covalent Bonding Ormentioning
confidence: 99%
“…[4,6] On account of high binding affinity and the wide scope of guests, cucurbit[n]uril (CB[n])-mediated host-guest complexes are ideal systems to bind peptides. [15][16][17][18][19][20] Urbach et al found that two FGG tripeptides can be complexed with CB [8] to form a peptide homodimer, exhibiting high binding strength (K ≈ 10 11 M -2 ). [15] This type of homodimer has been adopted as a versatile building block in the design and fabrication of supramolecular oligomers [21] and † These authors contributed equally to this work.…”
Section: Dimerization Of Peptides Through Covalent Bonding Ormentioning
confidence: 99%
“…[4,6] On account of high binding affinity and the wide scope of guests, cucurbit[n]uril (CB[n])-mediated host-guest complexes are ideal systems to bind peptides. [15][16][17][18][19][20] Urbach et al found that two FGG tripeptides can be complexed with CB [8] to form a peptide homodimer, exhibiting high binding strength (K ≈ 10 11 M -2 ). [15] This type of homodimer has been adopted as a versatile building block in the design and fabrication of supramolecular oligomers [21] and polymers, [22,23] supramolecular hydrogels, [24,25] and protein/peptide assemblies.…”
Section: Dimerization Of Peptides Through Covalent Bonding Ormentioning
confidence: 99%
“…Most thermodynamic studies show that the complexation process is enthalpy driven in great part due to the displacement of high energy water molecules from the cavity of the host [ 102 , 105 , 106 , 107 , 108 ]. This hydrophobic effect can be complemented by attractive ion-dipole interactions between the protonated amino group of the biomolecules and the carbonyl group of the cucurbituril ( Figure 7 ) [ 35 , 44 , 109 ]. In the case of the binding of aromatic amino acids by CB7, the process is also enthalpy driven with unfavorable negative entropy contributions.…”
Section: Receptors For Amino Acidsmentioning
confidence: 99%
“…These types of tripeptides show sub micromolar affinities towards CB8 and are also a plausible target for the detection of proteins by their N -terminal, seeing as, despite methionine being a common site of excision, large amino acids in the position next to Met can block the binding of the enzymes that catalyze this process, which distinguishes these N -terminal sequences from the excised ones [ 139 ]. Additionally, this functionality of the macrocycle can be used as a protection against excision of the N -terminal, for proteins presenting these sequences [ 109 ].…”
Section: Recognition Of Peptides: Taking Inspiration In Naturementioning
confidence: 99%